2022
DOI: 10.3390/en15155727
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Bacterial Cellulose Separators for Nickel-Zinc Batteries

Abstract: The need for energy-storing technologies with lower environmental impact than Li-ion batteries but similar power metrics has revived research in Zn-based battery chemistries. The application of bio-based materials as a replacement for current components can additionally contribute to an improved sustainability of Zn battery systems. For that reason, bacterial cellulose (BC) was investigated as separator material in Ni-Zn batteries. Following the biotechnological production of BC, the biopolymer was purified, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Combining bacterial cellulose with Al 2 O 3 , Ulfa et al achieved a higher crystallinity than that of pure bacterial cellulose as well as increased porosity, electrolyte absorption, and conductivity, suggesting the use of this composite as a battery separator [ 159 ]. Heydorn et al investigated bacterial cellulose separators especially for nickel–zinc batteries and found high hydroxide and zincate ion diffusion as well as high electrolyte uptake for a porous separator and better zincate shielding for a denser separator, while combining both resulted in slower cell aging and less ZnO in the pores of the separator [ 160 ]. For Li-ion batteries, Chen et al suggested a bacterial cellulose/chitosan separator whose pore size could be tailored, as depicted in Figure 10 [ 161 ].…”
Section: Bacterial Biopolymers For Batteriesmentioning
confidence: 99%
“…Combining bacterial cellulose with Al 2 O 3 , Ulfa et al achieved a higher crystallinity than that of pure bacterial cellulose as well as increased porosity, electrolyte absorption, and conductivity, suggesting the use of this composite as a battery separator [ 159 ]. Heydorn et al investigated bacterial cellulose separators especially for nickel–zinc batteries and found high hydroxide and zincate ion diffusion as well as high electrolyte uptake for a porous separator and better zincate shielding for a denser separator, while combining both resulted in slower cell aging and less ZnO in the pores of the separator [ 160 ]. For Li-ion batteries, Chen et al suggested a bacterial cellulose/chitosan separator whose pore size could be tailored, as depicted in Figure 10 [ 161 ].…”
Section: Bacterial Biopolymers For Batteriesmentioning
confidence: 99%
“…The growth of bacteria was limited when sucrose was used as a carbon source, probably due to the long pathway to convert sucrose into UDP-glucose. Some authors claimed that sucrose gave insignificant progress to cellulose production (Heydorn, Lammers, Gottschling, & Dohnt, 2023). However, the variation of sucrose amount differentiated the BC membrane growth, thickness and water-holding capacity properties (AL-Kalifawi et al, 2014;Jagannath, Kalaiselvan, Manjunatha, Raju, & Bawa, 2008).…”
Section: Production Yield and Thickness Of Bc Membranesmentioning
confidence: 99%
“…Seddiqi et al (2021) and Keshk (2014) stated that the composition of culture media and the variation of carbon sources had affected the surface area, porosity properties and production yield of BC membranes. Previously said that utilisation of sucrose as a primary carbon source at certain concentrations can provide higher water holding and porosity value instead of glucose, fructose and glycerol, however lesser in yield and thickness of BC membrane (Heydorn, Lammers, Gottschling, & Dohnt, 2023;Al-Shamary & Al-Darwash, 2013). In addition, Ruka, Simon and Dean (2013) claimed that sucrose could produce a consistently high yield and thicker BC membrane, indirectly affecting pore size, porosity and water-holding properties.…”
Section: Introductionmentioning
confidence: 99%
“…While BNC producers can catabolize many carbon sources, each species exhibits a sugar preference. For instance, glucose is preferentially utilized for K. xylinus, followed by lactose, 37 while Gluconacetobacter hansenii (G. hansenii) prefers sucrose and Komagataeibacter rhaeticus prefers mannitol. 38 More importantly, although enhanced BNC yield is undoubtedly most desirable for 3D biofabrication, other properties such as high mechanical integrity may also be advantageous.…”
Section: Role Of the Carbon Source In Bnc Productionmentioning
confidence: 99%